Phenological and physical characteristics and fatty acids of olive trees from the south of Minas Gerais, Brazil - Oliveira, Marcelo Caetano de; Ramos, José Darlan; Pio, Rafael; Cardoso, Maria das Graças (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the phenological and physical characteristics, the lipid content and the fatty acid profile of fruit of olive trees from Serra da Mantiqueira, at Minas Gerais state, Brazil. The cultivars Alto D’ouro, Arbequina, Galega, Grappolo 541, Grappolo 561, Grappolo 575, Negroa, Penafiel, Ropades 392 and Santa Catalina were evaluated in the 2008/09, 2009/10 and 2010/11 cycles. For fatty acids profile evaluation, crude oil was extracted from lipid‑rich cultivars. The flowering ranges from July to October, and the harvest from January to March. The earliest cultivar is 'Arbequina', and the latest ones are 'Galega', 'Grappolo 575' and 'Santa Catalina'. 'Grappolo 561' has fruit with the longest transverse diameter, and 'Grappolo 541' has fruit with the highest total mass. 'Arbequina' and 'Grappolo 561' show the highest lipid content.